Aesthetic Preference for Polygon Shape. (July 2015) - Friedenberg, Jay; Bertamini, Marco
Abstract shapes can vary in how much they are preferred by observers, but the key factors are still not well understood. In Experiment 1, observers rated the attractiveness of octagonal polygons that varied in contour length but had approximate constant area. Thus, the shapes differed in compactness. Shapes with partial symmetry were judged to be more attractive as were those with greater total contour length. In a second experiment, participants judged polygons with different numbers of concavities but with constant contour length. Shapes with more concavities were considered more attractive. The data demonstrate a preference for greater complexity—both in terms of contour length and as changes in the number of concavities.